Transformation of the potato variety Desiree with single or multiple resistance genes increases resistance to late blight under field conditions. (November 2015) - Haesaert, Geert; Vossen, Jack H.; Custers, René; De Loose, Marc; Haverkort, Anton; Heremans, Betty; Hutten, Ronald; Kessel, Geert; Landschoot, Sofie; Van Droogenbroeck, Bart; Visser, Richard G.F.; Gheysen, Godelieve
Abstract: Late blight, caused by Phytophthora infestans, remains the most devastating disease in potato resulting in economic costs that sum up 5.2 billion euros, globally. The use of resistant varieties is a powerful, viable and environmentally friendly alternative or supplement for the current, commonly deployed chemical control strategies. In this study, we set out to improve the susceptible potato variety Desiree by transformation with single or multiple late blight ( R ) resistance genes. Rpi-sto1, Rpi-vnt1.1 and a stack of Rpi-sto1 : Rpi-vnt1.1 : Rpi-blb3, were transformed and eight, eight, and ten independent transformants (events) respectively, were selected because of absence of vector backbone, low T-DNA copy number, responsiveness to the cognate Avr effectors, P. infestans resistance in detached leaf assays (DLAs) and preliminary field experiments. The performance of the selected events was studied under field conditions in The Netherlands and Belgium, after P. infestans inoculation and/or to natural late blight infection during two consecutive growing seasons. All selected events were more resistant than the non-transformed susceptible reference clone. The different individual R genes, however, contributed to different levels of resistance. The selected events were also compared to conventionally bred late blight resistant varieties with (partially) known R gene content. Generally, it was found that plants with single R genes showed a lower level of resistance than plants with R gene stacks. Only the events harbouring three late blight R genes remained unaffected until the end of the growing season, in both locations and in both growing seasons. Highlights: Transformation of the susceptible potato variety Desiree with single or multiple late blight ( R ) resistance genes. The potato transformants were tested in field trials in Belgium and The Netherlands during two years. All selected events were significantly more resistant than Desiree wild type in field trials in The Netherlands and Belgium. Plants with single R genes showed a lower level of resistance than plants with R gene stacks. The events harbouring three late blight R genes were immune until the end of the growing season.